Relationship of Vaginal Bacteria and Inflammation With Conception and Early Pregnancy Loss Following In-Vitro Fertilization - Linda O. Eckert; Donald E. Moore; Dorothy L. Patton; Kathy J. Agnew; David A. Eschenbach (Hindawi Limited, 2003)
Objective: The aim of this study was investigate the impact of vaginal flora and vaginal inflammation on conception and early pregnancy loss following in-vitro fertilization (IVF).